2012
DOI: 10.1177/1745691612462587
|View full text |Cite
|
Sign up to set email alerts
|

The Long Way From α-Error Control to Validity Proper

Abstract: Several influential publications have sensitized the community of behavioral scientists to the dangers of inflated effects and false-positive errors leading to the unwarranted publication of nonreplicable findings. This issue has been related to prominent cases of data fabrication and survey results pointing to bad practices in empirical science. Although we concur with the motives behind these critical arguments, we note that an isolated debate of false positives may itself be misleading and counter-productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(89 citation statements)
references
References 58 publications
4
79
0
Order By: Relevance
“…The result that 2 out of 3 papers containing nonsignificant results show evidence of at least one false negative empirically verifies previously voiced concerns about insufficient attention for false negatives (Fiedler, Kutzner, & Krueger, 2012). The Fisher test proved a powerful test to inspect for false negatives in our simulation study, where three nonsignificant results already results in high power to detect evidence of a false negative if sample size is at least 33 per result and the population effect is medium.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The result that 2 out of 3 papers containing nonsignificant results show evidence of at least one false negative empirically verifies previously voiced concerns about insufficient attention for false negatives (Fiedler, Kutzner, & Krueger, 2012). The Fisher test proved a powerful test to inspect for false negatives in our simulation study, where three nonsignificant results already results in high power to detect evidence of a false negative if sample size is at least 33 per result and the population effect is medium.…”
Section: Discussionsupporting
confidence: 82%
“…Cohen (1962) and Sedlmeier and Gigerenzer (1989) already voiced concern decades ago and showed that power in psychology was low. Fiedler et al (2012) contended that false negatives are harder to detect in the current scientific system and therefore warrant more concern. Despite recommendations of increasing power by increasing sample size, we found no evidence for increased sample size (see Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purely verbal and imprecise theories, however, ultimately become non-falsifiable as the absence of evidence can always be explained in terms of an infinite number of possible moderators suppressing or boosting the hypothesized effects. To avoid this issue, theory-driven hypotheses should predict specific situations and constellations for which bilingual advantages are expected, but also such in which no effects are expected to occur (Fiedler, Kutzner, & Krueger, 2012;see also Paap, 2014;Paap & Greenberg, 2013).…”
Section: Does the Bilingual Advantage Emerge Only For Specific Tasks mentioning
confidence: 99%
“…On the other hand, Bower 6 simply identifies the problem as one resulting from "closed thinking". These two psychologists, plus others 12,15,55 , decry this situation. That is, that too many of the mainline psychological theorists dismiss or ignore the work of others as being a threat to their own 56 .…”
Section: An Undervalued Disciplinementioning
confidence: 99%